Synthesis of Zinc-Nitrogen-Codoped Zirco-Titania Composite (Zn-N-Codoped ZT) as a Photocatalyst for Photodegradation of Phenol Under Visible Light Irradiation - Utami, Nadya Putri; Kurniawan, Rian; Pradipta, Mokhammad Fajar; Syoufian, Akhmad (Indonesian Journal of Chemistry, 2025)
Zinc (Zn) and nitrogen (N) were introduced as codopants in zirco-titania (Zn-N-codoped ZT) composite photocatalyst. This research primarily aimed to investigate the codoping effect of Zn and N in ZT composite for the photodegradation of phenol under visible light irradiation. The composite was prepared through the sol-gel method, where a suspension of ZrO2 mixed with Zn dopant (wZn/wTi = 1–9%) and N dopant (wN/wTi = 10%) was added dropwise to TTIP in ethanol solution. Calcination was conducted at the temperature of 500, 700, and 900 °C. FTIR shows an increasing absorbance at 1095 cm−1 as the increasing Zn up to 5%. XRD reveals that Zn-N cooping influences anatase and rutile crystallization above 700 °C. SEM-EDX of 5Zn-N-ZT-500 displays a spherical and homogeneous morphology. Photodegradation of 10 mg L−1 phenol solution under visible light irradiation was conducted to evaluate the photocatalytic activity. The composite with 5% Zn and 10% N calcined at 900 °C achieved the lowest band gap of 2.90 eV. The highest phenol degradation percentage after 120 min irradiation, 51.96%, was attained by the composite containing 5% Ni and 10% N calcined at 500 °C (kobs = 8.4 × 10−3 min−1).